Disrupting household food consumption through experimental HomeLabs: Outcomes, connections, contexts. (November 2017) - Devaney, Laura; Davies, Anna R.
This article explores the implications of conceptualising, designing and implementing experimental sites seeking to support more sustainable home-based eating practices, or HomeLabs for brevity. Building on earlier phases of practice-oriented participatory backcasting and transition framework construction, the HomeLabs involved collaboration with public, private and civil society sectors and with the members of participating households. These collaborations identified a suite of supportive socio-technological, informational and governance interventions that mimicked, as far as possible, the characteristics of promising practices for sustainable eating developed through backcasting and transition planning. The implemented interventions enabled householders to question, disassemble and reconfigure their eating practices onto more sustainable pathways across the integrated practices of food acquisition, storage, preparation and waste management. This process generated manifold insights into household eating practices, and this article focuses specifically on key outcomes of the HomeLabs, and the significance of social context, social relations and micropolitics of everyday life in shaping those outcomes. In particular, the HomeLabs findings reinforce calls to connect, combine and align product, regulatory, informational and motivational supports across the interdependent practices of eating (acquisition, storage and preparation and waste recovery) to optimise transitions towards sustainability. Offering a lens to interrogate interventions for sustainable food consumption in the home, this article provides a novel exercise in operationalising social practice theory.